RETRACTED: INTERVENSI BREATHING EXERCISE DAPAT MENURUNKAN TINGKAT KECEMASAN SISWA BIMBINGAN BELAJAR SAKURA - Toto Aminoto (Jurnal Ilmu dan Teknologi Kesehatan, 2018)
This is statement notice to inform and make consideration review related to an article entitled: “INTERVENSI BREATHING EXERCISE DAPAT MENURUNKAN TINGKAT KECEMASAN SISWA BIMBINGAN BELAJAR SAKURA”, Vol 5, No 2, pp: 162 – 170, Maret 2018. This paper has been found to be in violation of the Jurnal Ilmu dan Teknologi Kesehatan Publication principles and has been retracted. This article comprises an analogous material as published in Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), Vol 2 No 1, pp. 57-61, 2018. The document related to the article, including its content and supplementary article, has been removed from Jurnal Ilmu dan Teknologi Kesehatan. Hence, reasonable effort should be made to remove all references to this article.